Mechatronic Reconfigurable Intelligent‐Surface‐Driven Indoor Fifth‐Generation Wireless Communication - Heijun Jeong; Eiyong Park; Ratanak Phon; Sungjoon Lim (Advanced Intelligent Systems, 2022)
Reconfigurable intelligent surface‐assisted wireless networks have been proposed to overcome the current technical issues in fifth‐generation (5G) wireless communication systems. Generally, the beam control functions of a reconfigurable intelligent surface require the independent phase control of the unit cells, and each unit cell requires an active device. Although reconfigurable intelligent surfaces are considered a promising solution for 5G and sixth‐generation (6G) wireless communication, their practical implementation faces a bottleneck at high frequencies (e.g., with the millimetre‐wave spectrum) because they require a large number of active devices, leading to high costs, parasitic effects, increased design complexity, and modulated signal distortion. Herein, a mechatronic reconfigurable intelligent surface is reported for indoor millimetre‐wave wireless communication. Our mechatronic device strengthens the innovative reflective beam control functions through rotatable unit structures and rack gear systems. Furthermore, the criteria required for future 5 G wireless communication are experimentally verified by transmitting and receiving quadrature phase‐shift keying 16‐/32‐/64‐quadrature amplitude modulation signals based on 5 G new radio (NR) frequency range two standards for indoor environments.